A mechanism to regulate sovereign debt restructuring in the euro area - Jochen Andritzky; Désirée I. Christofzik; Lars P. Feld; Uwe Scheuering (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2018)
To make the no-bailout clause credible and enhance the effectiveness of crisis assistance, a consistent institutional and legal framework is needed to ensure that private creditors contribute to crisis resolution. Getting activated as part of ESM crisis assistance, we propose a novel two-stage mechanism that allows for postponing the fateful distinction between liquidity and solvency crises: At the onset of a ESM program, the framework demands an immediate maturity extension if the debt burden is high, followed by deeper debt restructuring if postcrisis debt proves unsustainable. The mechanism can be easily implemented by amending ESM guidelines and compelling countries to issue debt with Creditor Participation Clauses (CPCs). As debt is rolled over, the mechanism gradually phases in, leaving countries time to reduce debt. Given that private sector involvement reduces financing needs, the ESM could provide longer programs and more time for reforms.
Keywords: 330